2011
DOI: 10.1017/s1368980011003053
|View full text |Cite
|
Sign up to set email alerts
|

Maternal work hours in early to middle childhood link to later adolescent diet quality

Abstract: Objective: Previous studies on maternal work hours and child diet quality have reported conflicting findings possibly due to differences in study design, lack of a comprehensive measure of diet quality and differing ages of the children under investigation. The present study aimed to prospectively examine the impact of parental work hours from age 1 year to age 14 years on adolescent diet quality. Design: Multivariate linear regression models were used to examine independent associations between parents' work … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 27 publications
0
17
0
1
Order By: Relevance
“…Children of mothers who worked part-time were less likely to eat "less healthy eating" compared with children of mothers employed full-time, suggesting that part-time work may provide opportunities to plan and provide healthier food (Sweeting & West, 2005). Fathers working part-time may increase their ability to assist with meal preparation or other lifestyle activities (Li et al, 2012). Overall findings demonstrate that fathers working part-time may find it difficult to meet the nutritional needs and promote healthy food choices for their children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Children of mothers who worked part-time were less likely to eat "less healthy eating" compared with children of mothers employed full-time, suggesting that part-time work may provide opportunities to plan and provide healthier food (Sweeting & West, 2005). Fathers working part-time may increase their ability to assist with meal preparation or other lifestyle activities (Li et al, 2012). Overall findings demonstrate that fathers working part-time may find it difficult to meet the nutritional needs and promote healthy food choices for their children.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have found negative associations between the full‐time employment of mothers and FV consumption amongst children aged 5–14 years (Bauer, Hearst, Escoto, Berge, & Neumark‐Sztainer, ; Datar et al, ; Hawkins et al, ; Zarnowiecki, Ball, Parletta, & Dollman, ). A longitudinal Australian study has suggested that children of mothers who were working full‐time at age 1 year had a lower than average diet quality score (foods from six major food groups) at age 14 years (Li, O'sullivan, Johnson, Stanley, & Oddy, ). Previous study has suggested that children (aged 5 years) whose mothers worked part‐time were more likely to consume sugar sweetened beverages than children whose mothers had never been employed (Hawkins et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Constraints on mothers' time allocation for child health promoting activities have been viewed as the primary pathway linking maternal employment to childhood BMI. Longer maternal work hours have been linked to less time spent on grocery shopping and meal preparation (Cawley and Liu, 2012), greater consumption of prepared food (Cawley and Liu, 2012) and low quality diet (Li et al, 2011), and longer TV viewing hours and internet use in children (Datar et al, 2014;Fertig et al, 2009;Hawkins et al, 2009). Research has also examined these factors as mechanisms linking maternal employment to child BMI (Anderson, 2012;Brown et al, 2010;Datar et al, 2014;Fertig et al, 2009;Speirs et al 2014;Ziol-Guest et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly 30 dietary indices including nutrients, foods/food groups, or a combination of both have been developed or modified for children from the United States (toddlers, 2 to 18 years), [4][5][6][7][8][9][10][11][12][13] Australia (infants, toddlers, 4 to 16 years), [14][15][16][17][18] To take the Continuing Professional Education (CPE) quiz for this article, log in to www.eatrightPRO.org, go to the My Account section of the My Academy Toolbar, click the "Access Quiz" link, click "Journal Article Quiz" on the next page, and then click the "Additional Journal CPE quizzes" button to view a list of available quizzes. CPE quizzes are available for 1 year after the issue date in which the articles are published.…”
mentioning
confidence: 99%